A novel sensor based on electropolymerized substituted-phenols for pH detection in unbuffered systems. Issue 126 (9th December 2015) - Dai, Chencheng; Crawford, Lynne P.; Song, Peng; Fisher, Adrian C.; Lawrence, Nathan S.
Abstract : Polymeric waves associated with the electrochemical oxidation of salicylaldehyde and its derivatives exhibit Nernstian responses to pH variations in both buffered and unbuffered media. Abstract : This work summarizes the electrochemical response of a range of substituted phenols, including salicylaldehyde and salicylic acid, for use as a voltammetric pH sensor for the determination of pH in both buffered and unbuffered media. Suitable candidates are identified and mechanistic insights into oxidation mechanism of the electro-polymerization by comparing with other substituted phenols are given. Square wave voltammetry measurements suggest the peak achieved through the electrochemical polymerization directly after the 1-electron 1-proton oxidation for both salicylaldehyde and salicylic acid shows a Nernstian response with good definition through a pH range from 2 to 10. In addition, hydrogen bonding enables the compound to sense the pH of unbuffered solutions with an error of less than 1%.